148 Orthogeriatrics, Just the Beginning. (16th September 2019) - Smyth, Hannah; Hearne, Siofra; Monahan, Pheadra; Bermingham, Rebecca; Nawab, Sidra; Ameen, Hadeer; Timmons, Shirley; Mahapatra, Anant; Bhuachalla, Bláithín Ní; Lynch, Olwyn; Basit, Mian; Mulroy, Martin; et al.
Abstract: Background: The most common cause of admission to the orthopaedic ward are low trauma falls resulting in a hip fracture. These fragility fractures occur in older, frail, multi-morbid patients and they are associated with a high mortality rate and significant loss of independence. The Irish Hip Fracture Database is a national clinical audit that aims to improve hip fracture care and patient outcomes. Using the Irish Hip Fracture Standards, we aimed to audit the care of hip fracture patients in an Irish Model 3 Hospital pre- and post- implementation of an orthogeriatrics service. Methods: Local Irish Hip Fracture Database was reviewed to assess the six Irish Hip Fracture Standards prior and 4 months following the introduction of a consultant-led dedicated orthogeriatrics service. Results: There were 63 hip fracture patients (mean age 81) in the pre-service group and 69 (mean age 81) in the post-service group. Standard 1: 3.2% of hip fractures were admitted to the orthopaedic ward within 4 hours in the pre-service group versus 18.8% post-service introduction (national average 11%, 2017). Standard 2: 67.9% underwent surgery within 48 hours and during working hours versus 67.8% (national average 69%, 2017). Standard 3: 3.5% developed a pressure ulcer during their stay pre-service versus 1.6% post-service (national average 3%, 2017). Standard 4: 4.8% were assessed by a Geriatrician pre-service versus 84% post-service (national average 50%, 2017). Standard 5: 24.6% received a bone health assessment versus 87.5% post-service (national average 73%, 2017). Standard 6: 1.8% received a falls assessment prior to discharge versus 82.8% post-service (national average 47%, 2017). Conclusion: The introduction of a dedicated orthogeriatrics service has led to a more collaborative multi-disciplinary approach to patient care with evidence of improvements in all Irish Hip Fracture Standards. Commitment to a resourced orthogeriatric service providing rapid comprehensive geriatric assessments is essential to advance improvements in older patients' care.